Efektivitas Pengawasan Otoritas Jasa Keuangan (OJK) Dalam Menjamin Keamanan Dana Nasabah di Era Perbankan Digital : Studi Kasus Bank Syariah Indonesia - Aini, Ailia Nur; Girsang, Rachel; Putri, Amelia Juliana; Suwarsit, Suwarsit (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In the modern digital era, technological developments have driven major changes in the banking industry, enabling people to carry out convenient and efficient online transactions. This progress increases the tendency of people to save money in banks for the security of their assets, because the banking system is considered safer with the support of supervision by institutions such as the Financial Services Authority (OJK). Banks not only function as depositors of funds, but also play an important role in national economic growth through providing access to financing, lending and distributing monetary policy. Bank Syariah Indonesia (BSI), as one of the sharia-based banks in Indonesia, has adopted digital banking to strengthen services to customers according to sharia principles. Supervision of digital banks, especially by the OJK and Bank Indonesia, aims to protect customers through strict regulations regarding data security, transparency and fair treatment. In the case of cyber attacks such as ransomware that hit BSI, this security challenge shows the importance of increasing coordination between OJK, the National Cyber and Crypto Agency (BSSN), and related institutions to speed up response and recovery. This case underscores the importance of evaluating regulations and increasing the effectiveness of OJK supervision, especially in preparedness to face cyber threats, technology investment and customer education in digital banking